Role of spacer cations and structural distortion in two-dimensional germanium halide perovskites. Issue 31 (16th July 2021) - Chiara, Rossella; Morana, Marta; Boiocchi, Massimo; Coduri, Mauro; Striccoli, Marinella; Fracassi, Francesco; Listorti, Andrea; Mahata, Arup; Quadrelli, Paolo; Gaboardi, Mattia; Milanese, Chiara; Bindi, Luca; et al.
Abstract : The role of the organic spacer on the properties of Ge-based layered perovskites has been highlighted. Abstract : The elucidation of the structure–property correlation in 2D metal halide perovskite is a key issue to understand the dependence of optical properties on structural distortions and to design novel tailored materials. To extend the actual knowledge on this kind of correlation for lead-free materials, here we report four novel 2D germanium bromide perovskites, namely A2 GeBr4 with A = phenylethylammonium, PEA, Br-phenylethylammonium, BrPEA, F-phenylethylammonium, FPEA, and benzylammonium BZA. A dependence of the band gap value and emission characteristics in terms of Stokes shift and peak width has been highlighted and correlated with the octahedral distortion parameters. In addition, by comparing the actual results with previous data on analogous Sn- and Pb-based materials, we observed an intrinsic increased distortion induced by germanium, particularly on the octahedral bond elongation and bond angle variance, and less on the Ge–Br–Ge bond angle. The structural and optical investigation, together with density functional theory simulations, clarified the role of different structural distortion parameters on the optical properties for a series of 2D Ge-containing perovskites, thus providing novel clues for the future design of layered lead-free materials.